2019
DOI: 10.1029/2019je006050
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Impact Glasses: Probing the Moon's Surface and Constraining its Impact History

Abstract: Lunar impact glasses, formed during impact events when the regolith is quenched during the ejecta's ballistic flight, are small samples whose information can lead to important advances in studies of the Moon. For example, they provide evidence that constrains both the compositional evolution of the lunar crust and the timing of the lunar impact flux starting at ~4,000 million years ago. They are abundant in the lunar regolith and retain geochemical information that tells us where and when they formed. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 181 publications
(308 reference statements)
0
26
0
2
Order By: Relevance
“…Because the PGs were derived from the mantle sources, they would provide valuable geochemical information of the lunar interior and the early differentiation of the Moon (Saal et al., 2008; Shearer & Papike, 1993). During the impact processes (from massive basin‐forming impacts to tiny micrometeorite impacts), impact glasses would be generated by melting and subsequently quenching of lunar surface diverse materials (Papike et al., 1998; Zellner, 2019). These glasses would retain a geochemical memory of their fused target materials and impact chronology (Delano, 1991; Zellner, 2019; Zellner et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the PGs were derived from the mantle sources, they would provide valuable geochemical information of the lunar interior and the early differentiation of the Moon (Saal et al., 2008; Shearer & Papike, 1993). During the impact processes (from massive basin‐forming impacts to tiny micrometeorite impacts), impact glasses would be generated by melting and subsequently quenching of lunar surface diverse materials (Papike et al., 1998; Zellner, 2019). These glasses would retain a geochemical memory of their fused target materials and impact chronology (Delano, 1991; Zellner, 2019; Zellner et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During the impact processes (from massive basin‐forming impacts to tiny micrometeorite impacts), impact glasses would be generated by melting and subsequently quenching of lunar surface diverse materials (Papike et al., 1998; Zellner, 2019). These glasses would retain a geochemical memory of their fused target materials and impact chronology (Delano, 1991; Zellner, 2019; Zellner et al., 2009). In addition, impact processes also can generate nonmelt shocked glasses (e.g., maskelynite) by a solid‐state transition (e.g., Jaret et al., 2015; Kim et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While most impact glass ages record events <3 Ga (Zellner, 2019), our model predicts that the large volumes of melt products that are present in the surface regolith should have formed during the basin-forming period (Figure 4b). As impact glasses only make up about ∼3-5% of the regolith (McKay et al, 1991), it is possible that a large part of these impact melt products can be found as melt rocks in the regolith.…”
Section: Implications For Sample Interpretationsmentioning
confidence: 89%
“…Previous studies found an apparent excess of ages <0.5 Ga of impact glass spherules (Culler et al., 2000; Levine et al., 2005; Zellner & Delano, 2015). As an example, Figure 6b shows the relative abundance of the 40 Ar‐ 39 Ar ages of 128 lunar impact glass (70 spheres and 58 shards) assessed by Zellner (2019). One explanation for the excess of impact glass in this period is an increase in the impact flux during the late Copernican (Culler, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation